Romanian Literature in the German Press: Translation, Cultural Mediation and Reception - Chira, Oxana (Didactica Danubiensis, 2026)
This article examines how contemporary Romanian-language literature from Romania and the Republic of Moldova is represented in the German-speaking press, focusing on the mediating roles of translation, translators, and press discourse in shaping reception and symbolic legitimation. Prior Work: The study builds on reception aesthetics (Jauss, 1982), paratext theory (Genette, 1997), translation studies and translator (in)visibility (Venuti, 1995), and sociological approaches to literary circulation and center–periphery dynamics (Casanova, 2004). Approach: A qualitative discourse-analytical approach is applied to a curated corpus of press-based paratexts: review notices and critical summaries (e.g., Deutschlandfunk; Frankfurter Rundschau; FAZ; NZZ; Süddeutsche Zeitung; Die Welt) and an institutional interview-format conversation (IKGS München). The analysis focuses on recurring frames, evaluative patterns, and translator positioning. Results: The press reception oscillates between aesthetic recognition and contextualization through post-/Soviet history, migration, violence, and geopolitical threat narratives. Translators appear as key cultural mediators; their work is explicitly praised and used as a quality seal, while press discourse simultaneously legitimizes authors through event- and institution-driven paratexts. Implications: The findings highlight the press as a gatekeeping arena that constructs interpretive frames for “(semi-)peripheral” literatures and influences cultural promotion, publishing decisions, and readership expectations in the German-language literary field. Value: The article contributes a focused, theory-informed reading of concrete German-language reception materials and demonstrates how translation and press paratexts jointly produce visibility, meaning, and value for Romanian-language literature from Romania and the Republic of Moldova abroad.